Assessing Post Usage for Measuring the Quality of Forum Posts - Chai, Kevin; Hayati, Pedram; Potdar, Vidyasagar; Wu, Chen; Talevski, Alex (IEEE, 2010)
It has become difficult to discover quality content within forums websites due to the increasing amount of UserGenerated Content (UGC) on the Web. Many existing websites have relied on their users to explicitly rate content quality. The main problem with this approach is that the majority of content often receives insufficient rating. Current automated content rating solutions have evaluated linguistic features of UGC but are less effective for different types of online communities. We propose a novel approach that assesses post usage to measure the quality of forum posts. Post usage can be viewed as implicit user ratings derived from their usage behaviour. The proposed model is validated against an operational forum using Matthews Correlation Coefficient to measure performance. Our model serves as a basis of exploring content usage to measure content quality in forums and other Web 2.0 platforms.